Changes in gender relations in advertisement show on formula milk in television - Arizal Mutahir (Faculty of Social and Political Science, Universitas Airlangga, 2019)
In addition to selling products, formula milk advertisements also displayed an overview of what, who, and how is the Indonesian children’s identity. The process of constructing a gender perspective of Indonesian children occurred through the representation of children in these advertisements. This paper sought to read advertisements on formula milk in connection to gender relations. The purpose of this paper was to find out how the identity and gender of Indonesian children represented in formula milk advertisement. The constructionist approach used in this paper. Roland Barthes’s semiotic method used to read the child’s description and the child’s gender relations represented in the ad. The data of this paper were 45 adverts of formula milk from eight different brands that aired on television throughout 2011. In the reading process, it revealed that the description of gender roles in formula milk advertisements was a new form of gender relations in Indonesia. In advertisements, there was a mother figure who is still concerned with domestic roles. However, the boundary between domestic space and public space had been fading. The appearance of men had undergone modifications. Fathers were displayed interacting with his children in a friendly manner. This change in appearance did not necessarily change gender stereotypes. Boys were still dominant. They showed as healthy and smart. It had implications for gender ideas that were embedded and expressed in the appearance of children. Boys showed preparing to stare at the future with all the advantages attached to them. Children who showed advertisements of formula milk are boys who look contemporary, creative and come from the middle class.